Integration of Pancasila Values in Industrial Relations: A Trade Union Perspective in Multinational Companies - Sutrisno, Jemy Rengge; Irawati, Arista Candra (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2025)
Â This article analyzes the role of the Unit Leadership Council (PUK) of SP LEM SPSI at PT Steel Center Indonesia in developing industrial relations based on Pancasila values. The study emphasizes the integration of ideological foundations and practical strategies in advocating for workers' rights and fostering harmonious work relations. A qualitative descriptive method is employed, gathering data through observation, interviews, and document study. The findings reveal that PUK functions not only in normative roles within Collective Labor Agreement (CLA) negotiations but also as a transformative social agent through economic advocacy programs and social collaboration. Pancasila values are implemented through organizational activities such as bipartite communication, cadre consolidation, and cooperative management. These results demonstrate that trade unions can become a collective force not only to protect rights but also to promote social justice and sustainable welfare in the workplace.